(untitled) (Italian Review of Legal History, 2021)
The matter on the excessive duration of the judicial processes and its damaging consequences about the effects of the legal protection has always been one of the main issues in the relationship between justice and public opinion. Since the Italian unification, the problem has been mainly considered from the point of view of both judicial process reforms and judicial system reforms, without, however, providing adequate means to affect the organization of the structure and the personnel. It is just a short time since our legal system provided protection resources based on the principle of a fair duration of the judicial process, established in Article 111 of the Constitution. Whereas, since the beginning of the twentieth century, the disciplinary liability of judges, due to the delay in filing judicial orders, has represented one of the main resource not only to contain the most serious events (nowadays they cause even fiscal damage by disservice) but also to restore credibility in the judicial activity for the complicated dynamics related to the relationship between judiciary and society. Both the matters on the disciplinary liability of judges and the judiciary independence are interwoven in Italian history after unification and they had to find a delicate equilibrium. If during the liberal age and the Fascism, the disciplinary liability – according to the nineteenth-century model of the judge as an officer integrated in the state apparatus – allowed the control over judges – which was largely guaranteed, directly or not, by the executive power –, in republican Italy, instead, it fulfilled the aim to ensure the regular execution of the judicial activity thanks to a self-government system and to a different judge’ role inside the judicial system. The disciplinary bodies that were called to evaluate the judges’ conduct – the Supreme Disciplinary Court before and then after the year 1958 the Disciplinary Division of the Superior Council of the Judiciary – have realized a balance between the requests for reducing the long time frames in justice and the need to protect the prestige of judges. Referring to the case law of the Disciplinary Division of the Superior Council of the Judiciary, the Castelli reform introduced a standardization of disciplinary wrong, including the delay in filing judicial orders. It is regulated by art. 2 paragraph 1 letter q, of Legislative Decree of 23 february 2006 no. 109, and in accordance with it, the «repeated, serious and unjustified delay to carry out the job in the exercise of their duties» constitutes a wrong; «it is supposed that a delay is not serious when it does not exceed three times the period provided for by the law to carry out the job, except it may be proved otherwise». Such prediction represents already an improvement over the last years, where the disciplinary judge – in the absence of a rule considering the conduct of the ‘idle’ judge as a particular illegal case – could punish the most striking cases in a discretionary and variable manner, and not without contradiction. So these cases showed a clear violation by the judge who was blamed for a lack of diligence and his negligence was often accompanied by a complaint from the lawyers. At present in accordance with the provisions, three different and concurrent conditions must exist for the delay to be illegal: reiteration, seriousness of the delay and a lack of justification. These conditions (that are here studied according to the case law) are therefore all essential for the punishment of the delays. This study aims to determine if the case law measures, in the absence of suitable regulatory means for avoiding or at least containing the phenomenon of the slowness of proceedings, firstly, by the Supreme Disciplinary Court and, later, by the Disciplinary Division of the Superior Council of the Judiciary which had to punish the wrong of each judge, have been able to find a difficult balance between the standards of performance and a bearable workload. Furthermore if they were able to contain satisfactorily both the judicial process time and the delays, which are some of the main goals of the National Recovery Plan and Resilience.